Enhancing the Competitiveness of Micro and Small Enterprises (MSEs) in Bandung City Through Financial Management and Product Certification Assistance (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The Community Service activity, themed on enhancing the competitiveness of Micro and Small Enterprises (MSEs) in Regol Subdistrict, Bandung City, through financial management assistance and product certification, was carried out for 10 culinary MSE actors. It aimed to improve the quality of financial management to support business advancement, and to increase product quality and consumer trust through Halal-certified products. The activities included material delivery, workshops on supporting technology use, and direct assistance. The increase in post-test scores after 9 material deliveries indicates that the training had an impact on improving participants' understanding. The largest percentage increase in score was in the Business Licence material at 62.3%, and the smallest was in the Product Branding material at 7.6%.  Feedback from participants showed that they were satisfied and benefited from all the activities.